PENGARUH CUSTOMER EQUITY TERHADAP WORD OF MOUTH PERGURUAN TINGGI SWASTA - Rifqi Suprapto (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
Consumer confidence in a product or brand will have an impact on increasing consumer loyalty to the brand or product concerned. One form of consumer loyalty to the company product or brand is shown in the form of Word of Mouth. This also applies within the scope of the college in which the student confidence for what he has received during the conduct of university education will be formed into a satisfaction for students. Therefore, the purpose of this study was to determine the effect of Customer Equity in Word of Mouth in Higher Education.This study is a survey research with quantitative descriptive research type. The population in this study Yogyakarta Muhammadiyah University Students Strata-1 semester five upwards, with sample collection method used a numbering 150. The questioner that has been tested previously to 30 respondents and tested the validity and reliability that results in a 100% said the question is valid and feasible to be used. The research method using SEM analysis test used AMOS.The result from this study is no positive influence brand equity and the value equity towards WoM (Word of Mouth). However, relationship equity had a positive influence on the value of WoM (Word of Mouth).Keywords: Word of Mouth, Customer Equity, and University